2021
DOI: 10.1007/s11886-021-01570-8
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid Annuloplasty: Transcatheter Approaches

Abstract: Purpose of Review New transcatheter techniques to perform tricuspid annuloplasty are evolving and are introduced into the clinical routine. Yet, clinical experience is limited. Recent Findings Currently, 3 different techniques for tricuspid annuloplasty have been used in larger clinical cohorts. They can be divided into direct annuloplasty techniques and suture plication techniques. The largest clinical evidence is related to direct annuloplasty te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Surgical techniques are extremely effective in reducing or eliminating TR. [ 5 ] Preferably, annuloplasty techniques either suture based or involving annuloplasty rings should be used for the treatment of FTR instead of valve replacement. [ 5 ] Furthermore, relatively high mortality rates (8.8%–9.7%) have been reported after conventional surgery for isolated TR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgical techniques are extremely effective in reducing or eliminating TR. [ 5 ] Preferably, annuloplasty techniques either suture based or involving annuloplasty rings should be used for the treatment of FTR instead of valve replacement. [ 5 ] Furthermore, relatively high mortality rates (8.8%–9.7%) have been reported after conventional surgery for isolated TR.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] Preferably, annuloplasty techniques either suture based or involving annuloplasty rings should be used for the treatment of FTR instead of valve replacement. [ 5 ] Furthermore, relatively high mortality rates (8.8%–9.7%) have been reported after conventional surgery for isolated TR. [ 6 ] In order to address this problem, several catheter-based techniques that mimic the surgical annuloplasty techniques have been developed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently published reports on RCA deformation after interventional tricuspid annuloplasty revealed that RCA deformations without flow limitation recover after a few days ( 6 ). Thus, the unreported rate of RCA deformations without flow limitation might be even higher, as it seems not to be clinically harmful ( 12 ). Yet, long-term data were still lacking.…”
Section: Discussionmentioning
confidence: 99%